“Icy” scarp exposures, “ice-rich” overburdens and ephemeral climate-warming at Mars' mid-latitudes in the very late Amazonian epoch - Richard J. Soare; Colman J. Gallagher; James B. Garvin; Jean-Pierre Williams; Adam J. Hepburn; Francois Costard; Michelle Koutnik; An Y. Li (Icarus, 2025)

A Marine Isotope Stage 4 age for Pleistocene raised beach deposits near Fethard, southern Ireland - Colman Gallagher; Matt W. Telfer; Colm Ó Cofaigh (Journal of Quaternary Science, 2015)
Raised beach deposits around the Irish coast have been interpreted as interglacial or last glacial in age. On the south coast of Ireland, the Courtmacsherry Formation raised beach (CFB), near Fethard, County Wexford, was dated using optically stimulated luminescence (OSL). This site was previously dated to Marine Isotope Stage (MIS) 6–5, but more recent dating of the CFB elsewhere along the south coast shows it is considerably younger (MIS 4–3). The OSL analyses in this paper aimed to determine if new dating would support the greater age of the Fethard raised beach or realign it with the CFB. The new OSL ages place the formation of the Fethard raised beach between 57 ± 6 and 45 ± 6 ka, with 53 ± 5 ka the most likely age if a single depositional event is assumed. This is consistent with OSL dates of the CFB elsewhere. An MIS 4–3 age has important implications in understanding the palaeogeography and timing of glaciation in Ireland, and requires a reassessment of regional relative sea level history. As the eustatic response to global ice volume resulted in lowered relative sea level during MIS 4–2, a crustal response to glaciation is implied by the new dates.